Inclusive and sustainable active mobility: recommendations for older adults in Montenegro - Popovic, Stevo; Babayigit Irez, Gonul; Masanovic, Bojan (Frontiers in Physiology, 2026)
This paper provides a perspective on inclusive and sustainable active mobility solutions for older adults in Montenegro, informed by research conducted in Podgorica and the wider region. Active mobility is a key factor influencing healthy ageing, social inclusion, and quality of life; however, its improvement requires a systemic approach connecting urban planning, public health, and social policy. In Montenegro, rapid urbanization, insufficient infrastructure, and limited intersectoral cooperation challenge the development of safe and accessible mobility options for older citizens. Using an analytical framework developed within two COST Actions and guided by the WHO “Age-friendly Cities” model, this perspective proposes recommendations aimed at improving accessibility, safety, and participation of older adults in public space. Special emphasis is placed on integrating GIS tools into local planning, introducing regular accessibility assessments, and involving older residents in decision-making processes. This perspective argues that inclusive and sustainable active mobility is not only an infrastructural requirement but also a public health priority that demands long-term, coordinated strategies aligned with European standards. It thereby contributes to advancing policy and planning efforts toward age-friendly urban development in emerging European contexts.